O processo de referenciação e a intertextualidade em acórdãos do Supremo Tribunal Federal e do Superior Tribunal de Justiça - Souza, Ana Pereira de (2014)
This dissertation is constituent of research line named Text and Discourse in Written and Oral Modalities. Its theme is The Reference Process and the Intertextuality in the Supremo Tribunal Federal and Superior Tribunal de Justiça s sentences. The general goal of this study has as purpose to contribute for a better comprehension of judicial texts, like Superior Court s sentences, to all kind of people, including those ones with no Law knowledge. The specific goals of this study have as purpose to identify and to analyze the nominalization process and the explicit intertextuality in Supremo Tribunal Federal and Superior Tribunal de Justiça s sentences and also to reflect on how those phenomena can give us clues for a better comprehension of those particular texts. The theoretical basis is in the Textual Linguistic and to reach our goals we research the following authors: Koch (2009), Mondada and Dubois (2003), Marcuschi (2007), Marquesi (2007), Lima and Feltes (2013), Roncarati (2010) and Cavalcante and other authors (2010) (in case of the reference process); Koch (2009), Roncarati (2010), Koch and Elias (2011a), Lima and Feltes (2013) and Silva and Custódio Filho (2013) (in case of reference strategies); Guimarães (2009), Koch (2009, 2010), Koch and Elias (2011a, 2011b), Francis (2003), Apothèloz (2003) and Conte (2003) (in case of anaphora); Koch, Bentes and Cavalcante (2008), Koch (2010), Guimarães (2009), Koch and Elias (2011a), Koch and Travaglia (2011), Fairclough (2001, 2008) and Marcuschi (2008) (in case of intertextuality). As result, we can say that there is a kind of recurrence to the same reference strategies and types of intertextuality showed in those texts, as if there was a kind of analysis pattern in the textual construction. Both reference strategies and types of intertextuality can help Portuguese Language speakers to build sense when they have to face and to decipher those judicial texts, like judicial sentences